Corrosion challenges in petroleum refinery operations: Sources, mechanisms, mitigation, and future outlook - Al-Moubaraki, Aisha H.; Obot, Ime Bassey (Journal of Saudi Chemical Society, 2021)
[Display omitted] •Corrosion is the number one enemy facing the petroleum refineries.•Many sources and mechanism of corrosion problems in the refining operations were discussed.•Material selection, cathodic protection, corrosion inhibitors, and metal coating are some mitigation methods of corrosion used in refineries.•The existing knowledge gap in literature and future research directions were proposed. Corrosion is one of the most important challenges facing petroleum refineries. It has received wide attention in recent decades due to the continued dependence of the global economy on industries based on oil and natural gas. With annual corrosion cost estimated at billions of dollars, suitable corrosion mitigation approaches are required to prevent assets failure due to the menace of corrosion. A vast amount of information on corrosion mitigation in the petroleum refinery is available. However, it is spread in various scientific publications, and gathering such information is critical in building a body of knowledge on the corrosion issues arising from refinery operations. A perusal of the literature reveals that a review focused on corrosion mitigation in the refinery is scarce. So, a comprehensive and up-to-date review of corrosion mitigation in the refinery is timely. In the present review, the corrosion issues at the different units of the refinery are presented. Physicochemical basics in corrosion at refinery units have been considered. In addition, the sources of the corrosion problem and the current mitigations approaches such as engineering design, cathodic protection, the use of corrosion inhibitors and metal coating were discussed. Finally, the existing knowledge gaps were identified, and future research directions were proposed. The review concludes that corrosion in the refinery has not received wide attention in the literature like other corrosion issues in the petroleum industry. The advancement of research in the area of real time and accurate prediction models, collection of sufficient data regarding ammonium bisulfide (NH4HS) corrosion in the refinery plant, development of novel smart nanomaterials coating, and environmentally friendly high temperature corrosion inhibitors are needed for effective mitigation of refinery corrosion.